Generation and characterization of CRISPR/Cas9-mediated MEN1 knockout BON1 cells: a human pancreatic neuroendocrine cell line - Monazzam, Azita; Li, Su-Chen; Wargelius, Hanna; Razmara, Masoud; Bajic, Duska; Mi, Jia; Bergquist, Jonas; Crona, Joakim; Skogseid, Britt (Scientific reports, 2020)
Among patients with the rare diagnosis of pancreatic neuroendocrine tumor (P-NET), a substantial proportion suffer from the inherited cancer syndrome multiple endocrine neoplasia type 1 (MEN1), which is caused by germline mutations of the MEN1 suppressor gene. Somatic mutations and loss of the MEN1 protein (menin) are frequently also found in sporadic P-NETs. Thus, a human neuroendocrine pancreatic cell line with biallelic inactivation of MEN1 might be of value for studying tumorigenesis. We used the polyclonal human P-NET cell line BON1, which expresses menin, serotonin, chromogranin A and neurotensin, to generate a monoclonal stable MEN1 knockout BON1 cell line (MEN1-KO-BON1) by CRISPR/Cas9 editing. Changes in morphology, hormone secretion, and proliferation were analyzed, and proteomics were assessed using nanoLC-MS/MS and Ingenuity Pathway Analysis (IPA). The menin-lacking MEN1-KO-BON1 cells had increased chromogranin A production and were smaller, more homogenous, rounder and grew faster than their control counterparts. Proteomic analysis revealed 457 significantly altered proteins, and IPA identified biological functions related to cancer, e.g. , posttranslational modification and cell death/survival. Among 39 proteins with at least a two-fold difference in expression, twelve are relevant in glucose homeostasis and insulin resistance. The stable monoclonal MEN1-KO-BON1 cell line was found to have preserved neuroendocrine differentiation, increased proliferation, and an altered protein profile.